FLASH MEDIA IMPLEMENTATION IN TEACHING READING - Arbryan, Anggry (Lembaga Penelitian Unswagati Cirebon Indonesia, 2018)
The media if used in the educational setting will complement the teaching-learning process. It will make the English language teaching better and more effective, and will also âenhance the studentsâ ability and to attract studentsâ attention in order to understand and experiment with the language. This research aims at: (1) describing how Flash Media used in teaching and learning of reading, (2) describing the other media that are used to support Flash Media in teaching and learning of reading, and (3) describing the difficulties of implementing Macro Media Flash Player in teaching and learning of reading. This research applies a case study method as one of qualitative research. The subject of the research were the English teacher and students on the ninth grade of one junior high school in Wonogiri. The data were collected through non-participant observation, interview, and documentation. In analyzing the data, the researcher used interactive model of analysis data by Miles and Huberman. The findings of the research show that the implementation of the Macromedia Flash Player has shown positive relation in supporting teaching and learning process. The other supporting media were also play the role to complete the teaching and learning experiences. It is hoped that the result can encourage English teachers to explore more medium and implement it in teaching and learning.